Macroeconomic Policies to Increase Social Mobility and Growth in Bolivia - Lykke E. Andersen; Alice Brooks; Alejandro F. Mercado (Institute for Advanced Development Studies (INESAD), 2004)
Poverty in Bolivia continues to be among the highest in Latin America despite decades of concerted national and international efforts to reduce it. Bolivia has meticulously followed the recommendations of the Washington consensus at the same time as external aid has been generous and foreign direct investment has boomed. Nevertheless, average productivity and incomes remain at the same low level as they were 50 years ago. This paper suggests that the failure of previous development policies is due to a lack of social mobility in the country. Without social mobility, there is little incentive for people to invest in human and physical capital, and without investment there cannot be productivity growth. In addition, the lack of social mobility implies an inefficient use of human capital, and it hinders the construction of efficient social mechanisms for redistribution and consumption smoothing over the life-cycle.
Keywords: E60; I32; J12; J13; 330; Social Mobility; Development; Public Policy; Bolivia